On the design of a secure and anonymous publish-subscribe system - Mulamba Kadimbadimba, Dieudonne, author; Ray, Indrajit, advisor; Ray, Indrakshi, committee member; Vijayasarathy, Leo, committee member (Colorado State University. Libraries, 2012)
The reliability and the high availability of data have made online servers very popular among single users or organizations like hospitals, insurance companies or administrations. This has led to an increased dissemination of personal data on public servers. These online companies are increasingly adopting the publish-subscribe as a new model for storing and managing data on a distributed network. While bringing some real improvement in the way these online companies store and manage data in a dynamic and distributed environment, publish-subscribe is also bringing some new challenges of security and privacy. The centralization of personal data on public servers has raised citizens' concerns about their privacy. Several security breaches involving the leakage of personal data have occured, showing us how crucial this issue has become. A significant amount of work has been done in the field of securing the publish-subscribe. However, all of this research assumes that the server is a trusted entity, an assumption which ignores the fact that this server can be honest but curious. This leads to the need to develop a means to protect publishers and subscribers from server curiosity. One solution to this problem could be to anonymize all communications involving publishers and subscribers. This solution will raise in turn another issue which involves how to allow a subscriber to query a file that was anonymously uploaded in the server by the publisher. In this work, we propose an implementation of a communication protocol that allows users to asynchronously and anonymously exchange messages and that also supports a secure deletion of messages.
Keywords: anonymous communication; publish-subscribe; computer security